Forecasting GDP all over the world using leading indicators based on comprehensive survey data - Johanna Garnitz; Robert Lehmann; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2019)
Comprehensive and international comparable leading indicators across countries and continents are rare. In this paper, we use a free and instantaneous available source of leading indicators, the ifo World Economic Survey (WES), to forecast growth of Gross Domestic Product (GDP) in 44 countries and three country aggregates separately. We come up with three major results. First, for more than three-fourths of the countries or country-aggregates in our sample a model containing one of the major WES indicators produces on average lower forecast errors compared to a benchmark model. Second, the most important WES indicators are either the economic climate or the expectations on future economic development for the next six months. And third, adding the WES indicators of the main trading partners leads to a further increase of forecast accuracy in more than 50% of the countries. It seems therefore reasonable to incorporate economic signals from the domestic economy's main trading partners.
Keywords: E17; E27; E37; 330; world economic survey; economic climate; forecasting GDP